“Gestão da tradução e da interpretação de Libras e língua portuguesa no Instituto Federal do Espírito Santo” - Burgarelli, Eliana Firmino (2022)
Due to the strengthening of inclusive education policy in the 21st century, translation and interpreting of/to sign languages have become regular activities in educational institutions. Considering the need to expand the knowledge about the institutional dynamics involving these activities, this thesis aims to analyze policies for translation and interpreting of Brazilian Sign Language (Libras) and Portuguese within the Instituto Federal do Espírito Santo (Ifes). To this end, we analyze two sets of official documents that regulate practices of translation and interpreting of Libras and Portuguese at Ifes: (i) one consists of documents external to the institution, such as laws and decrees; and (ii) the other, of documents internal to the institution, such as public notices and selection processes for hiring translators and interpreters, and regulations, guidelines and resolutions. Based on the perspective of authors from the field of Translation Policies (MEYLAERTS, 2011; SANTOS; FRANCISCO, 2018; SANTOS; VERAS, 2020), Language Policies (MAHER, 2013; SEVERO, 2013; SPOLSKY, 2004; 2009; 2016; LAGARES, 2018) and that of Language Law (PHILLIPSON; SKUTNABB-KANGAS, 2017; ABREU, 2019; 2020), the concept of translation and interpreting management, inspired by Language Management Theory (SPOLSKY, 2016), is used as an analytical tool. Based on the analysis of the documents, four units of meaning were conceived regarding the management of translation and interpreting of Libras and Portuguese at Ifes: (i) translation and interpreting of Libras and Portuguese as a right of the Brazilian deaf population; (ii) the aspects concerning the education of translators and interpreters; (iii) the elements related to the hiring of these professionals; and (iv) the provision of translation and interpreting in the domain of the Institute. Based on this, it was possible to consider the importance of understanding the management of translation and interpreting of public services in an educational context, highlighting political aspects that constitute it at the institutional level and produce effects on the processes of inclusion and education of signing deaf. The thesis offers theoretical and methodological contributions to discussions and investigations in the field of Translation Studies and Interpreting Studies intertwined with Applied Linguistics.